PRODUCTION OF CELLULASE AND REDUCING SUGAR FROM OIL PALM EMPTY FRUIT BUNCH BY Streptomyces hirsutus ISOLATE 12.3.A - Nurkaya, Hamka (PROSIDING SEMINAR KIMIA, 2013)
This research aimed to utilize the oil palm empty fruit bunch for the production of reducing sugar. The oil palm empty fruit bunch (OPEFB) is the palm oil industry waste which composed of lignocellulosic material. Utilization microbial as an organism which can degrade a lignocellulosic biomass into simple sugars is a way to reduce the environmental problem. A potential of using OPEFB to accelerate cellulase activity and reducing sugar production by cellulolytic microorganism was tested. The high cellulase activity and reducing sugar producing actinomycetes isolate 12.3.A that was isolated from the oil palm plantation area in Phetchaburi, Thailand was used in this study. The isolate 12.3.A was preliminary appointed to be Streptomyces hirsutus from the result of 16S-rRNA gene analysis. The optimal conditions for cellulase activity and reducing sugar production of S. hirsutus isolate 12.3.A were determined. The best yields were derived from culturing the cells at pH 7, 30Â°C, substrate concentration of 1% and ammonium sulfate as nitrogen sources for 6 days incubation. The highest cellulase activities and reducing sugar production from OPEFB as substrate were 0.71 U/ml and 3.82 mg/ml, respectively.